ANALISIS PERKEMBANGAN BUMDES RANTAU KASAI DESA TAMBUSAI UTARA - Mila Sari Juwita; Liya Rosliana (Fakultas Ekonomi Universitas Pasir Pengaraian, 2023)
The development of the economic base in rural areas has long been carriedout by the government through various programs. However, these efforts have not yielded satisfactory results. This has become a special concern of the government, so policies related to economic empowerment were born which were carried out by collecting and institutionalizing economic activities which were fully managed by the village community, namely Village Owned Enterprises (BUMDES). The users of Rantau Kasai BUMDes funds are in the business of 3 Kg LPG gas bases and savings and loans. The aim of the research is to find out whether the influence of Rantau Kasai Village Owned Enterprises has on business activities and village economic development. The research method used in this research isa quantitative method using multiple linear regression data analysis. The study population was 136 people with a sample data of 101 people obtained using the slovin formula. The independent variable (X) is the value of benefits, community participation and innovation, while the dependent variable (Y) is business activity and village economic development. The tests used are validity, reliability, multiple linear regression analysis, coefficient of determination test, f test and t test with the help of SPSS. The results showed that the data analysis using the multiple linear regression method obtained for each variable, namely the value of benefits or social (X1), community participation (X2), and innovation (X3) is known to have a t count > t table and a probability value (sig t) smaller than 0.05, so it can be concluded that all research variables have a positive and significant effect on business activities and economic development in North Tambusai Village.